2013
DOI: 10.1111/ijal.12014
|View full text |Cite
|
Sign up to set email alerts
|

Is ELF more effective and fair than translation? An evaluation of the EU's multilingual regime

Abstract: The management of multilingualism in the European Union (EU) has become an increasingly debated issue. Some argue that ‘English as a lingua franca' (ELF) should help solve many of the attendant challenges. The claim is sometimes made that ELF, as a multilingual way of using English, is no longer dependent upon the practices and representations of native speakers and therefore poses no threat to linguistic diversity or to fairness. In this article, we question the relevance of the concept of ELF from a language… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(26 citation statements)
references
References 21 publications
0
26
0
Order By: Relevance
“…English as a global language has always been embedded in the tension between being a global lingua franca, on the one hand, and the national language of the UK, USA, and other Anglophone countries, on the other. Using English as global lingua franca eo ipso privileges those countries who do not have to invest significant national resources into learning it as a foreign language (Gazzola and Grin 2013). Consequently, it is not surprising that this investment in English is now being subjected to critical interrogation (Li 2020a).…”
Section: Language Challenges Of the Covid-19 Crisismentioning
confidence: 99%
“…English as a global language has always been embedded in the tension between being a global lingua franca, on the one hand, and the national language of the UK, USA, and other Anglophone countries, on the other. Using English as global lingua franca eo ipso privileges those countries who do not have to invest significant national resources into learning it as a foreign language (Gazzola and Grin 2013). Consequently, it is not surprising that this investment in English is now being subjected to critical interrogation (Li 2020a).…”
Section: Language Challenges Of the Covid-19 Crisismentioning
confidence: 99%
“…These claims, notably supported by few empirical evidence by their authors, currently seem be rather wishful thinking, as is in my opinion sufficiently proven by Fiedler (2010Fiedler ( , 2011 with emphasis that ELF communication does exist, but is by no means culturefree) and Gazzola & Grin (2013): ELF is still English, and learners of English still try to achieve native speaker qualities, as the research of Jenkins (2007) herself has shown. On the one hand it is of course laudable to absolve the L2-users of Engli sh of the i nferi or posi tion of a defici ent speaker and to val orize their language use, but on the other hand the dogma of a "neutral" ELF has the consequence of neglecting and playing down the huge difference in effort required by L1 and L2 speakers of English to reach an acceptable level of proficiency in the language -for English native speakers it is still nearly nothing, in comparison to thousands of hours for speakers of other languages.…”
Section: English As a Lingua Francamentioning
confidence: 75%
“…These institutional documents confirmed my premises about the lack of an overarching political vision with each institution expressing their position on multilingualism according to their functional characteristics and needs. As a final step, I examined concrete language practices in major EU institutions focusing especially on the European Parliament basing my research on empirical studies carried by Ammon (2012), Fischer (2010), Forchtner (2014), Gazzola (2006Gazzola ( , 2013Gazzola ( , 2014 Kraus (2008), Kruse & Ammon (2013) Krzyzanowski & Wodak (2010.…”
Section: Language Policy Analysismethodologymentioning
confidence: 99%